Strategy for Implementing 3A in the Development of Religious Tourism at the Kapal Bosok Mosque (Study: Community of Darangong Village, Curugmanis Village, Serang-Banten) - Mayasari; Budiaman; Fatgehipon, Abdul Haris (Indonesian Journal of Entrepreneurship and Startups, 2023)
This study aims to find out in depth the application of the 3A strategy (Attractions, Activities and Accessibility) in the Religious Tourism of the Kapal Bosok Mosque. The 3A concept is one of the requirements for developing a tourist destination. Each tourist destination must have its own uniqueness and characteristics that make it a tourist attraction. This study uses a qualitative approach, with data collection techniques namely observation, interviews, field notes and documentation. The results of the study show that the religious tourism of the ship bosok mosque is a religious tourism destination that has implemented the 3A strategy in its development where the attractions or appeal of the religious tourism of the ship bosok mosque lie in the shape of the building and history. Activities or activities for tourists have been provided by the manager and accessibility is sufficient and becomes a level of convenience for tourists